Continuity of Inclusive Education and Psychological and Pedagogical Support for Persons with Special Educational Needs - Rubtsov, V.V.; Alekhina, S.V.; Khaustov, A.V. (Psihologo-pedagogičeskie issledovaniâ, 2019)
In the article the authors set a goal setting for the current consideration of the prerequisites of lifelong education and psychological and pedagogical support for people with special educational needs, the content of the concept of continuing education is determined. Presented are data from studies examining the attendance of educational institutions for children with disabilities, as well as information reflecting the intentions of parents to continue their education for children under 15 years of age, information about people with disabilities studying in vocational educational programs that emphasize the relevance of the continuing education of persons with disabilities, reflect a low the degree of readiness of parents to continue their education with children with disabilities, the need to build a system of continuous support I have children, adolescents and adults with disabilities in all regions of Russia, forming the basis for the continuity of personal educational path, the importance of developing a scientific approach to its study. Specific conditions for building a tracking model are defined. The experience of research and organization of continuous support of individuals with autism spectrum disorders is considered. It is concluded that it is necessary to discuss the topics of psychological and pedagogical support at the stage of obtaining a profession and employment. The value of unique practices in building an individual educational trajectory is noted. В статье авторами задается целевая установка на актуальное рассмотрение предпосылок непрерывного образования и психолого-педагогического сопровождения лиц с особыми образовательными потребностями, определяется содержание понятия непрерывности образования. Представлены данные исследований, рассматривающих вопросы посещаемости образовательных учреждений детьми-инвалидами, а также сведения, отражающие намерения родителей по продолжению обучения детей до 15 лет, сведения об инвалидах, обучающихся по профессиональным образовательным программам, которые подчеркивают актуальность проблемы непрерывного образования лиц с инвалидностью, отражают невысокую степень готовности родителей к продолжению образования их детьми-инвалидами, необходимость построения системы непрерывного сопровождения детей, подростков и взрослых с ограниченными возможностями здоровья во всех регионах России, формирования личностной основы для непрерывности образовательной траектории, важность разработки научного подхода к ее изучению. Определены специальные условия для построения модели сопровождения. Рассматривается опыт исследования и организации непрерывного сопровождения лиц с расстройствами аутистического спектра. Сделан вывод о необходимости обсуждения тематики психолого-педагогического сопровождения на этапе получения профессии и трудоустройства. Отмечается ценность уникальных практик в построении индивидуальной образовательной траектории.